Magnetic field and ISM in the local Galactic disc. Issue 1 (26th February 2019) - Sofue, Y; Nakanishi, H; Ichiki, K
Abstract: A correlation analysis is obtained among Faraday rotation measure, H i column density, and thermal and synchrotron radio brightness using archival all-sky maps of the Galaxy. A method is presented to calculate the magnetic strength and its line-of-sight (LOS) component, volume gas densities, effective LOS depth, and effective scale height of the disc from these data in a hybrid way. Applying the method to archival data, all-sky maps of the local magnetic field strength and its parallel component are obtained, which reveal details of local field orientation.